Research on monometallic plate piezoelectric ceramic column array broadband high sensitivity transducer. (30th March 2023) - Zhao, Jihang; Wang, Hongwei
Highlights: By improving the process, a highly sensitive piezoelectric material has been produced, and the sensitivity of the transducer has been increased using the material as a sensitive element. The theoretical analysis derives the equivalent circuit of a highly sensitive piezoelectric material, and the resonance conditions are solved. The bandwidth of the transducer operation is extended by means of band superposition. Abstract: A kind of broadband and highly sensitive underwater acoustic transducer with increased bandwidth and sensitivity is proposed. The effective electromechanical coupling coefficient of the piezoelectric material and the sensitivity of the transducer are improved by using air instead of polymer in the piezoelectric composite and by covering the upper surface of the piezoelectric column array with metal plates. Besides, the operating bandwidth of the transducer is increased through bandwidth superposition. Theoretical analysis is conducted to determine the resonance conditions of the monometallic plate piezoelectric ceramic array material as a sensitive element. With the dimensional parameters of the sensitive component determined by means of finite element simulation, the transducer is designed and produced. According to the test results, the bandwidth of the transducer reaches 60 kHz, the maximum transmit voltage response is 152.1 dB and the receiving sensitivity is −182.5 dB, which is effective in improving both the receiving sensitivity and bandwidth of the transducer.